Blood Collection from Mice and Hematological Analyses on Mouse Blood. Issue 2 (June 2013) - Rathkolb, Birgit; Fuchs, Helmut; Gailus‐Durner, Valérie; Aigner, Bernhard; Wolf, Eckhard; Hrabě de Angelis, Martin
Abstract: Basic phenotyping of inbred mouse strains and genetically modified mouse models usually includes the determination of blood‐based parameters as a diagnostic screen for genotype effects on metabolism and organ function. A broad range of analytes, including hematological parameters, can be reliably determined in mouse blood, if appropriate samples are available. Here we describe recommended techniques for blood collection from mice and the considerations that have to be taken into account to get adequate samples for hematological investigations. Furthermore, we describe established methods used in the German Mouse Clinic (GMC) to determine hematological parameters in the mouse. Curr. Protoc. Mouse Biol. 3:101‐119 © 2013 by John Wiley & Sons, Inc.